TL1A/TNFR2‐mediated mitochondrial dysfunction of fibroblast‐like synoviocytes increases inflammatory response in patients with rheumatoid arthritis via reactive oxygen species generation. (17th January 2020) - Al‐Azab, Mahmoud; Qaed, Eskandar; Ouyang, Xunli; Elkhider, Abdalkhalig; Walana, Williams; Li, Han; Li, Weiping; Tang, Yawei; Adlat, Salah; Wei, Jing; Wang, Bing; Li, Xia
Abstract : Rheumatoid arthritis (RA) is the major autoimmune destructive disease of joints with a complicated pathogenesis. The contribution of tumor necrosis factor‐like ligand 1A (TL1A) in RA pathogenesis, especially on fibroblast‐like synoviocytes (FLS), has been suggested clinically. The present study investigated the role of TL1A in mitochondrial dysfunction, induced oxidative stress in mitochondria, apoptosis resistance and the inflammatory response in FLS obtained from RA patients (RA‐FLS). RA‐FLS were incubated with TL1A and tumor necrosis factor receptor 2 (TNFR2) antagonist. Respiratory function, mitochondrial membrane potential and respiration associated genes of mitochondria were measured in both TL1A stimulated and non‐stimulated RA‐FLS. Additionally, the effects of TL1A on reactive oxygen species (ROS) production in mitochondria, apoptosis and the inflammatory response in RA‐FLS were also assessed. The role of TL1A in association between ROS generation, especially mitochondrial type and the inflammatory response, was evaluated by measuring inflammation‐related cytokines and signaling pathways using ROS inhibitors, diphenyleneiodonium chloride and Mito‐TEMPO (Sigma‐Aldrich, Miamisburg, OH, USA). We found that TL1A induced mitochondrial dysfunction by weakening mitochondrial respiration and membrane potential, which was blocked by a TNFR2 antagonist. Increased ROS synthesis in impaired mitochondria was observed with MitoSOX (Invitrogen, CA, USA) immunofluorescence staining in TL1A‐stimulated RA‐FLS but inhibited by a TNFR2 antagonist. TL1A influenced apoptosis resistance and inflammatory mediators via TNFR2. Inhibition of mitochondria‐derived ROS compromised the production of inflammatory factors in TL1A‐stimulated RA‐FLS, suggesting that mitochondrial dysfunction mediated by the TL1A/TNFR2 axis might amplify the inflammatory response via regulation of mitochondria‐derived ROS generation. Collectively, our results reveal that TL1A might be involved in making FLS more aggressive in RA pathogenesis via cell respiration interruption. Abstract : Tumor necrosis factor‐like ligand 1A (TL1A) stimulated fibroblast‐like synoviocytes (FLS) of rheumatoid arthritis (RA) patients via a novel receptor, TNF receptor 2 (TNFR2). The TL1A/TNFR2 axis induced mitochondrial dysfunction, cellular survival and the inflammatory ability of RA‐FLS. Furthermore, mitochondrial dysfunction mediated by the TL1A/TNFR2 axis may amplify an inflammatory response via reactive oxygen species regulation. Finally, TL1A was involved in making FLS more aggressive in RA pathogenesis via interruption of cellular respiration.